Supraclavicular Irradiation Induces Lymphedema in Breast Cancer Patients Treated with Axillary Lymph Node Dissection and Taxane-Containing Chemotherapy - Nanae Horisawa; Akiyo Yoshimura; Isao Oze; Masataka Sawaki; Masaya Hattori; Haruru Kotani; Ayumi Kataoka; Yuri Ozaki; Kazuki Nozawa; Yuka Endo; Daiki Takatsuka; Ayaka Isogai; et al. (The Breast Journal)
Purpose. Breast cancer-related lymphedema (LE) significantly impairs the patients’ quality of life. Axillary lymph node dissection (ALND) is a strong risk factor for LE in breast cancer surgery. In addition, postoperative administration of docetaxel (DTX) has been reported to be a risk factor for LE in patients who undergo ALND. Herein, we performed the risk of objective LE after ALND. Methods. Patients who visited the medical follow-up clinic between 12 November 2018 and 11 January 2019 and at least one year postoperatively were eligible for this study. The risk factors for objective LE according to taxane-containing regimen, radiation therapy, and body mass index and the effects of a taxane-containing regimen followed by supraclavicular irradiation on LE were examined. Results. A total of 214 patients were included in this analysis, and objective LE was observed in 52 patients (24%). Univariate and multivariate analyses showed that only supraclavicular field irradiation was a statistically significant risk factor for objective LE. In addition, the sequential use of taxane-containing regimens and supraclavicular RT was shown to be a more likely risk factor for LE than ALND alone. We also compared each taxane regimen with supraclavicular RT and found that DTX was more likely to be a risk factor for LE in cases of sequential use of supraclavicular RT than with ALND alone. However, when comparing DTX with supraclavicular RT and PTX with supraclavicular RT directly, there was no statistically significant difference in the risk of objective LE between the two groups. Conclusion. The risk for LE was more likely to be higher with the sequential use of taxane-containing chemotherapy and supraclavicular field irradiation. Therefore, management of LE is important in these cases.